Integrated positive electrode material, oxide-based solid-state lithium-carbon dioxide battery and preparation method

By constructing a multiphase transport interface and using highly conductive carbon materials and lithium-ion transport media in oxide-based solid-state lithium-carbon dioxide batteries, the transport and safety issues of liquid lithium-carbon dioxide batteries have been solved, achieving a solid-state battery design with high discharge potential and long lifespan.

CN121035240APending Publication Date: 2025-11-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410668595.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing liquid lithium-carbon dioxide batteries suffer from problems such as CO2 diffusion, lack of interface structure, thermal runaway, and dendrite growth in lithium metal anodes, which prevent them from meeting the requirements for high energy density, safety, and long lifespan.

Method used

An oxide-based solid-state lithium-carbon dioxide battery is designed by in-situ growing highly conductive carbon materials and loaded lithium-ion transport media on a current collector, combined with single-atom or nano-metal catalysts, to construct a multiphase transport interface and achieve rapid lithium-ion, electron, and carbon dioxide gas transport.

Benefits of technology

It achieves a high discharge potential of 3.05V and 260 cycles of reversible charge-discharge stability, improving the energy density and safety of the battery, and is suitable for high-energy-density and high-safety solid-state rechargeable batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035240A_ABST
    Figure CN121035240A_ABST
Patent Text Reader

Abstract

The invention discloses an integrated positive electrode material, an oxide-based solid-state lithium-carbon dioxide battery and a preparation method. The integrated positive electrode material comprises a current collector, an active component and a lithium ion transmission medium, wherein the active component and the lithium ion transmission medium are loaded on the current collector; a high-conductivity carbon material is grown on the surface of the current collector in situ; the active component comprises an active element, and the active element is selected from at least one of copper, nickel, cobalt and iron; the lithium ion transmission medium comprises a lithium element. The solid-state lithium-carbon dioxide battery composed of the integrated positive electrode, the oxide solid-state electrolyte and the metal lithium negative electrode disclosed by the invention has the advantages of high discharge potential of 3.05 V, 260 circles of reversible stable charge-discharge cycles and the like at room temperature, and the greenhouse gas CO2 is efficiently utilized; the solid-state secondary battery is expected to be a novel solid-state secondary battery with high energy density and high safety.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to an integrated positive electrode material and an oxide-based solid lithium-carbon dioxide battery and a preparation method, and belongs to the technical field of lithium-carbon dioxide batteries. BACKGROUND

[0002] In recent years, global warming caused by CO2-based greenhouse gases has become increasingly serious, and the greenhouse effect caused thereby brings many hazards. As the latest generation of energy storage batteries, lithium-carbon dioxide batteries have a high theoretical energy density (1876 Wh kg -1 ) and a discharge potential (~2.8 V), and have great potential in the field of carbon dioxide fixation and are expected to become a desirable long-distance power transmission energy storage device. However, the liquid lithium-carbon dioxide battery cannot meet the requirements of higher energy density, higher safety and longer service life for various application scenarios. Firstly, CO2 will diffuse to the negative electrode in the liquid electrolyte, causing serious side reactions of the lithium negative electrode. Secondly, the positive electrode side lacks abundant multi-phase interface structures for the transmission of electrons, lithium ions and CO2 gas. Thirdly, the safety problems such as thermal runaway caused by the narrow working temperature range of the organic electrolyte and the dendrite growth of the lithium metal negative electrode. SUMMARY

[0003] In order to overcome the deficiencies of the prior art, the application aims to design an oxide-based solid lithium-carbon dioxide battery and an integrated positive electrode thereof. By constructing a continuous multi-phase transmission interface of lithium ions, electrons and carbon dioxide gas and a single-atom or nanometer metal type high-efficiency catalyst, the high overpotential caused by the excessive interface resistance and the slow CO2 reduction and precipitation kinetics can be effectively avoided, and a high discharge potential of 3.05 V and 260 cycles of reversible charge-discharge stable cycles can be obtained.

[0004] According to a first aspect of the application, an integrated positive electrode material is provided, the integrated positive electrode material comprising a current collector and a lithium ion transmission medium supported on the current collector.

[0005] The surface of the current collector is in-situ grown with a high-conductivity carbon material.

[0006] The lithium ion transmission medium comprises a lithium element.

[0007] Optionally, the current collector further comprises an active component, and the active component comprises an active element.

[0008] Optionally, the active element is selected from at least one of copper, nickel, cobalt and iron.

[0009] Optionally, the current collector is selected from at least one of a stainless steel mesh and a nickel foam.

[0010] Optionally, the in-situ grown carbon material in the high-conductive carbon material is carbon nanotube.

[0011] According to a second aspect of the present application, a preparation method of the integrated positive electrode material is provided, and the preparation method comprises the following steps:

[0012] (1) heat treating the nitrogen-containing compound and the current collector under a non-active atmosphere to grow in-situ to obtain a current collector containing high-conductive carbon material;

[0013] (2) heating and drying II a mixture of lithium salt, polymer matrix, stabilizer, solvent, additive, and the current collector containing high-conductive carbon material to obtain the integrated positive electrode material.

[0014] Optionally, the preparation method comprises the following steps:

[0015] S1: heat treating the nitrogen-containing compound and the current collector under a non-active atmosphere to grow in-situ to obtain a current collector containing high-conductive carbon material;

[0016] S2: soaking the current collector containing high-conductive carbon material in a metal salt solution, rotary evaporating and drying I, and annealing under a non-active atmosphere to obtain a current collector containing metal;

[0017] S3: heating and drying II a mixture of lithium salt, polymer matrix, stabilizer, solvent, additive, and the current collector containing metal, and further vacuum drying III to obtain the integrated positive electrode material.

[0018] Optionally, in the step S1, the nitrogen-containing compound is selected from at least one of melamine, urea, and dicyandiamide.

[0019] Optionally, the mass ratio of the nitrogen-containing compound to the current collector is (1.0-2.0 g):(0.3-0.5 g).

[0020] Optionally, the heating rate of the in-situ growth is 2-10℃ / min. -1 The temperature of the in-situ growth is 600-800℃, and the time of the in-situ growth is 1-3h.

[0021] Optionally, the heating rate of the in-situ growth is independently selected from any value in 2℃ / min. -1 4℃ / min. -1 6℃ / min. -1 8℃ / min. -1 10℃ / min. -1 or a range value between any two of the above values.

[0022] Optionally, the temperature of the in-situ growth is independently selected from any of 600 °C, 650 °C, 700 °C, 750 °C, 800 °C or a range between any two of the aforementioned.

[0023] Optionally, the time of the in-situ growth is independently selected from any of 1 h, 1.5 h, 2 h, 2.5 h, 3 h or a range between any two of the aforementioned.

[0024] Optionally, in the step S2, the metal salt in the metal salt solution is selected from at least one of copper chloride, cobalt chloride, nickel chloride, ferrous chloride.

[0025] Optionally, the solvent in the metal salt solution is ethanol.

[0026] Optionally, the loading of the metal on the metal-containing current collector is 0.1-20%, the loading of the metal being calculated based on the amount of the metal salt in the metal salt solution.

[0027] Optionally, the loading of the metal on the metal-containing current collector is independently selected from any of 0.1%, 1%, 2%, 5%, 10%, 15%, 20% or a range between any two of the aforementioned.

[0028] Optionally, the temperature of the drying I is 50-80 °C and the time of the drying I is 6-12 h.

[0029] Optionally, the annealing comprises annealing I and annealing II.

[0030] Optionally, the heating rate of the annealing I is 2-10 °C min -1 , the temperature of the annealing I is 250-350 °C and the time of the annealing I is 2-5 h.

[0031] Optionally, the heating rate of the annealing I is independently selected from any of 2 °C min -1 , 4 °C min -1 , 6 °C min -1 , 8 °C min -1 , 10 °C min -1 or a range between any two of the aforementioned.

[0032] Optionally, the temperature of the annealing I is independently selected from any of 250 °C, 280 °C, 300 °C, 320 °C, 350 °C or a range between any two of the aforementioned.

[0033] Optionally, the time of the annealing I is independently selected from any of 2 h, 3 h, 4 h, 5 h or a range between any two of the aforementioned.

[0034] Optionally, the heating rate of the annealing II is 1-5 °C min-1 The temperature of the annealing II is 350-550℃, and the time of the annealing II is 2-5h.

[0035] Optionally, the heating rate of the annealing II is independently selected from any value in the group consisting of 1℃ / min -1 , 2℃ / min -1 , 3℃ / min -1 , 4℃ / min -1 , 5℃ / min -1 or a range value between any two of the above.

[0036] Optionally, the temperature of the annealing II is independently selected from any value in the group consisting of 350℃, 400℃, 450℃, 500℃, 550℃ or a range value between any two of the above.

[0037] Optionally, the time of the annealing II is independently selected from any value in the group consisting of 2h, 3h, 4h, 5h or a range value between any two of the above.

[0038] Optionally, in the step S1 and the step S2, the non-reactive atmosphere is independently selected from at least one of nitrogen, argon.

[0039] Optionally, in the step S3, the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate.

[0040] Optionally, the polymer matrix is poly(vinylidene fluoride-co-hexafluoropropylene).

[0041] Optionally, the stabilizer is butylated hydroxytoluene.

[0042] Optionally, the solvent is dimethyl sulfoxide.

[0043] Optionally, the additive is butanedinitrile.

[0044] Optionally, the amount ratio of the polymer matrix, the solvent, the lithium salt, the stabilizer, the additive is (0.2-0.6g):(2-5mL):(0.1-0.28g):(0.1-0.4g):(0.2-0.7g).

[0045] Optionally, the temperature of the drying II is 20-60℃, and the time of the drying II is 6-12h.

[0046] Optionally, the temperature of the vacuum drying III is 20-60℃, and the time of the drying III is 36-60h.

[0047] According to a third aspect of the present application, there is provided an oxide-based solid-state lithium-carbon dioxide battery comprising a positive electrode, a negative electrode, a solid-state electrolyte, an interface protection film and a battery housing;

[0048] The interface protection film is disposed between the positive electrode and the solid-state electrolyte and between the negative electrode and the solid-state electrolyte, respectively;

[0049] The positive electrode is selected from the integrated positive electrode material described above;

[0050] The negative electrode is metallic lithium;

[0051] The solid-state electrolyte is an oxide-type solid-state electrolyte;

[0052] The battery housing is a positive electrode-holed button cell.

[0053] Optionally, the oxide-type solid-state electrolyte is selected from at least one of Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), Li 1.3 Al 0.3 Ti 1.7 P3O 12 (LATP), Li 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO).

[0054] Optionally, the interface protection film comprises a lithium salt I and an ionic liquid.

[0055] Optionally, the lithium salt I is selected from at least one of lithium bis-trifluoromethanesulfonimide, lithium tetrafluoroborate.

[0056] Optionally, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate.

[0057] Optionally, a layer of electrolyte that can conduct Li + + is coated between the solid-state electrolyte and the positive and negative electrodes, and the electrolyte is composed of a lithium salt and an ionic liquid, wherein the lithium salt is lithium bis-trifluoromethanesulfonimide or lithium tetrafluoroborate, and the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide or 1-ethyl-3-methylimidazolium tetrafluoroborate.

[0058] According to a fourth aspect of the present application, there is provided a preparation method of the oxide-based solid-state lithium-carbon dioxide battery described above, the preparation method comprising the following steps:

[0059] (1) preparation of integrated positive electrode material;

[0060] (2) assembling the battery in the positive electrode hole button cell to obtain the oxide-based solid-state lithium-carbon dioxide battery.

[0061] As an optional implementation, the application is implemented by the following technical solutions:

[0062] The preparation method is specifically as follows:

[0063] Step one, growing high-conductivity carbon material on the surface of the current collector in situ, the carbon material is carbon nanotube;

[0064] Step two, preparing single-atom or nano-metal type catalyst material on the carbon nanotube, the single-atom or nano-metal type catalyst material is one or a combination of more than one of copper, nickel, cobalt, iron transition metal single atom and nano-particle, and the metal loading on the carbon nanotube is 0.1-20%;

[0065] Step three, introducing continuous lithium ion transmission medium on the surface of the current collector in situ to prepare an integrated solid-state lithium-carbon dioxide battery positive electrode.

[0066] Optionally, the step one is specifically as follows:

[0067] Step 1.1, laying 1-3 g of melamine on the bottom of the porcelain boat, placing a layer of carbon paper in the middle, and placing the current collector above it;

[0068] Step 1.2, placing the loaded porcelain boat in a tube furnace, and performing high-temperature heat treatment under N2 or Ar atmosphere, heating at a rate of 2-10 ℃min -1 to 600-800 ℃, and keeping the temperature for 1-3 h.

[0069] Optionally, the step two is specifically as follows:

[0070] Step 2.1, adding copper metal salt to anhydrous ethanol, and stirring ultrasonically to a transparent solution, the metal salt being one or a combination of more than one of anhydrous copper chloride, anhydrous cobalt chloride, anhydrous nickel chloride, and anhydrous ferrous chloride;

[0071] Step 2.2, soaking the current collector with carbon material in the ethanol solution containing copper metal salt, and performing rotary evaporation until the liquid is completely volatilized, and then placing it in a vacuum drying box for drying treatment at 50-80 ℃;

[0072] Step 2.3, drying the pole piece, and performing two high-temperature annealing treatments under N2 or Ar atmosphere respectively. The first heat treatment parameters are 2-10 ℃min -1heating rate of 1-5℃ / min to 250-350℃, and holding for 2-5h. -1 heating rate of 1-5℃ / min to 350-550℃, and holding for 2-5h.

[0073] Optionally, the step three is specifically:

[0074] Step 3.1, first, 0.2-0.6g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is dissolved in 2-5mL of anhydrous dimethyl sulfoxide (DMSO), stirring at 50-80℃ until the PVDF-HFP is completely dissolved; then, 0.1-0.28g of lithium bis-trifluoromethanesulfonimide and 0.1-0.4g of stabilizer butylated hydroxytoluene (BHT) are added, and continue to stir until dissolved; finally, 0.2-0.7g of butanedinitrile is added and continue to stir to obtain a uniform solution;

[0075] Step 3.2, the current collector prepared in step two is cut to a certain size and placed on a customized polytetrafluoroethylene (PTFE) mold, then the uniform solution is poured on the above-mentioned current collector, and dried at a temperature of 20-60℃ in a glove box for 36-60h until the DMSO is volatilized;

[0076] Step 3.3, finally, it is placed in a vacuum drying oven for 20-60℃ drying treatment for 36-60h, and finally an integrated positive electrode is obtained.

[0077] The application discloses an oxide-based solid-state lithium-carbon dioxide battery, which comprises a lithium sheet, a solid-state electrolyte, an integrated positive electrode and a battery shell; the solid-state electrolyte divides the whole battery into a positive electrode side and a negative electrode side; the positive electrode side is an integrated self-supporting positive electrode covered with a transition metal single-atom or nanoparticle catalyst material and a lithium ion transmission medium on a high-conductivity carbon material grown in situ; the negative electrode side is provided with a lithium sheet; and the solid-state lithium-carbon dioxide battery shell is a positive electrode with a hole. The application designs an integrated self-supporting positive electrode. In the application, a carbon nanotube self-supporting material is grown on the surface of a current collector in situ, one or more combinations of copper, nickel, cobalt, iron transition metal single atoms and nanoparticle catalysts are loaded on the surface, and a continuous lithium ion transmission medium is further introduced in situ. The integrated positive electrode is characterized in that a rapid lithium ion, electron and carbon dioxide gas multiphase transmission process is realized, and a high-efficiency single-atom or nanoparticle metal type catalyst is constructed to effectively decompose the discharge product.

[0078] The application can produce beneficial effects, including:

[0079] The application realizes the rapid multi-phase transmission of lithium ions, electrons and carbon dioxide gas, and accelerates the kinetics of CO2 reduction and evolution reaction by the design of an integrated self-supporting positive electrode. Compared with other solid-state lithium-carbon dioxide batteries, the discharge potential is lower than 2.8V, and the application successfully increases the potential to 3.05V. In the application, the integrated positive electrode side of the battery is provided with a single-atom or nano-metal type catalyst. According to the different positive electrode catalysts, the CO2 reduction products can be effectively regulated, and 260 reversible charge-discharge stable cycles can be realized. The oxide-based solid-state lithium-carbon dioxide battery and its integrated positive electrode can efficiently utilize the greenhouse gas CO2, and are expected to become a new type of solid-state secondary battery with high energy density and high safety. BRIEF DESCRIPTION OF DRAWINGS

[0080] Figure 1 FIG. 1 is a structural schematic diagram of an oxide-based solid-state lithium-carbon dioxide battery according to the application.

[0081] Figure 2 FIG. 4 is an X-ray diffraction pattern of the oxide-based solid-state electrolyte LAGP synthesized in Example 1 of the application.

[0082] Figure 3 FIG. 5 is a scanning electron microscope cross-sectional picture of the integrated positive electrode synthesized in Example 1 of the application, with a scale of 10 μm.

[0083] Figure 4 FIG. 6 is a constant capacity charge-discharge curve of Example 1 of the application.

[0084] Figure 5 FIG. 7 is a constant capacity charge-discharge cycle curve of Example 1 of the application.

[0085] Figure 6 FIG. 8 is a scanning electron microscope picture of the integrated positive electrode synthesized in Example 4 of the application, with a scale of 100.0 μm. DETAILED DESCRIPTION

[0086] The application will be described in detail below in conjunction with examples, but the application is not limited to these examples.

[0087] Unless otherwise specified, the raw materials in the examples of the application are purchased through commercial channels.

[0088] The battery performance of the application is tested in a LAND CT2001A system by using a constant current charge-discharge technology; the phase and crystallinity of the sample are analyzed by XRD, and the equipment model used is SmartLab, using a Cu target Kα ray The scanning speed is 10° / min -1 . The instrument equipment is characterized; the morphology of the sample is observed by SEM, and the equipment model used is Quanta 200F.

[0089] As shown in Figure 1 The oxide-based solid-state lithium-carbon dioxide battery of the present application comprises a negative electrode of lithium sheet, a solid-state electrolyte, an integrated positive electrode and a battery shell; the solid-state electrolyte divides the whole battery into a positive electrode side and a negative electrode side; the positive electrode side is an integrated self-supporting positive electrode covered with transition metal monatomic or nanoparticle catalyst material and lithium ion transport medium on the in-situ grown high-conductive carbon material; the negative electrode side is provided with a lithium sheet; and the solid-state lithium-carbon dioxide battery shell is a positive electrode with a hole in a button cell. The transition metal monatomic or nanoparticle catalyst material is one or a combination of copper, nickel, cobalt and iron, and further in-situ introduced with continuous lithium ion transport medium.

[0090] The energy storage mechanism of the oxide-based solid-state lithium-carbon dioxide battery of the present application is as follows: in the discharging process, lithium ions and electrons are dissociated from the metal lithium negative electrode, the lithium ions migrate to the positive electrode through the solid-state electrolyte, and the electrons reach the positive electrode through the external circuit; on the surface of the positive electrode, the lithium ions, the electrons and the carbon dioxide entering the system from the positive electrode react to generate lithium carbonate and carbon; in the charging process, the lithium carbonate and the carbon are reduced to carbon dioxide, lithium ions and electrons by catalysis, the carbon dioxide leaves the system through the positive electrode, and the lithium ions reach the negative electrode through the electrolyte and combine with the electrons reaching the negative electrode through the external circuit to generate metal lithium.

[0091] The overall reaction of the battery is:

[0092] Assembly of the battery: the prepared integrated positive electrode is quickly transferred into an argon-filled glove box (H2O value ≤0.01 ppm, O2 value ≤0.01 ppm), wherein the negative electrode uses a lithium sheet (a circle with a diameter of 14 mm), the solid-state electrolyte is an oxide-type solid-state electrolyte, and a layer of Li + conductive electrolyte is coated between the solid-state electrolyte and the positive and negative electrodes, specifically one of 1-ethyl-3-methyl imidazole bis(trifluoromethanesulfonyl) imide solution dissolving lithium bis(trifluoromethanesulfonyl) imide or 1-ethyl-3-methyl imidazole tetrafluoroboric acid dissolving lithium tetrafluoroborate. After the battery is assembled, the battery is placed in an air cell test mold, taken out of the glove box, CO2 gas is introduced, the Ar in the bottle is exhausted, and the battery is placed in an atmosphere filled with CO2 gas. Then the battery is placed in a constant temperature box at 25±2℃ for 12h to reach a stable state, and then the electrochemical performance test is carried out.

[0093] The preparation of the integrated positive electrode in the oxide-based solid-state lithium-carbon dioxide battery energy storage device is as follows:

[0094] Step one: in-situ growth of high-conductive carbon material on the surface of the current collector; the carbon-based material is carbon nanotube;

[0095] Step 1.1, spread melamine on the bottom of the boat, put a layer of carbon paper in the middle, and place the current collector on top;

[0096] Step 1.2, place the loaded boat in a tube furnace and perform high-temperature annealing treatment under N2 or Ar atmosphere.

[0097] Step two, prepare single-atom or nano-metal type catalyst materials, which are one or more combinations of copper, nickel, cobalt, iron transition metal single atoms and their nanoparticles;

[0098] Step 2.1, add metal salt to anhydrous ethanol and ultrasonically stir until a transparent solution is obtained;

[0099] Step 2.2, soak the current collector with carbon material in the ethanol solution containing metal salt, perform rotary evaporation until the liquid is completely volatilized, and then place it in a vacuum drying box for drying treatment;

[0100] Step 2.3, dry the positive electrode sheet and perform two high-temperature annealing treatments under N2 or Ar atmosphere.

[0101] Step three, introduce a continuous lithium ion transport medium in situ on the surface of the current collector to prepare an integrated solid-state lithium-carbon dioxide battery anode.

[0102] Step 3.1, first dissolve polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in anhydrous DMSO and stir at a certain temperature until PVDF-HFP is completely dissolved; then, add lithium bis-trifluoromethanesulfonimide and stabilizer BHT and continue stirring until dissolved; finally, continue stirring after adding butanedinitrile to obtain a uniform solution;

[0103] Step 3.2, cut the current collector prepared in step two to a certain size and place it on a customized polytetrafluoroethylene (PTFE) mold, then pour the uniform solution onto the current collector and heat it to a certain temperature in the glove box until the DMSO is volatilized;

[0104] Step 3.3, finally, place it in a vacuum drying box for drying treatment, and finally obtain an integrated anode.

[0105] The following is a specific description for specific data examples:

[0106] Example 1

[0107] (1) Take a stainless steel mesh current collector with a size of 3*6 cm, and clean it with acetone, ethanol, and water for multiple times, each time for at least 10 min.

[0108] (2) Spread 1.0g of melamine evenly on the bottom of a ceramic boat, place a layer of carbon paper in the middle, and place a stainless steel mesh current collector on top of it. In an Ar atmosphere, spray at 2℃ for 2 min. -1 The heating rate is increased to 600℃ and held for 1 hour.

[0109] (3) The stainless steel mesh with carbonized material after annealing was placed in an ethanol solution of anhydrous copper chloride for rotary evaporation at a speed of 30 rpm. -1 .

[0110] (4) The dried positive electrode sheet was subjected to two high-temperature annealing treatments under an Ar atmosphere. The parameters for the first heat treatment were 2℃ min. -1 The heating rate was increased to 250℃, held for 2 hours, removed, washed with ethanol, and dried in a vacuum drying oven; the second heat treatment parameters were 1℃ / min. -1 The heating rate was increased to 350℃ and held for 2 hours. The metal loading on the carbon nanotubes was 5%.

[0111] (5) The obtained electrode material is introduced in situ into the succinic acid-based solid electrolyte under an Ar atmosphere to form a continuous lithium-ion transport layer.

[0112] First, 0.2g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) was dissolved in 2mL of anhydrous dimethyl sulfoxide (DMSO) and stirred at 50℃ until PVDF-HFP was completely dissolved. Then, 0.1g of lithium bis(trifluoromethanesulfonyl)imide and 0.1g of stabilizer dibutylhydroxytoluene (BHT) were added and stirred until dissolved. Finally, 0.2g of succinate was added and stirred to obtain a uniform solution. The uniform solution was then poured onto the electrode material prepared in step (4), heated to 20℃ in a glove box, and dried for 36h until DMSO evaporated. Finally, it was placed in a vacuum drying oven and dried at 20℃ for 36h to obtain an integrated positive electrode.

[0113] (6) Battery assembly: Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP) is used as the solid electrolyte, and an integrated positive electrode and metallic Li are used as the positive and negative electrodes, respectively. A 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide protective film containing lithium bis(trifluoromethanesulfonyl)imide is coated between the positive and negative electrodes and the solid electrolyte. The battery is assembled in a coin cell with holes.

[0114] like Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of the oxide solid-state lithium-carbon dioxide battery in Example 1. It can be seen that the integrated cathode structure has a rich multiphase reaction interface of lithium ions, electrons and carbon dioxide gas.Figure 2 X-ray diffraction pattern of the oxide solid-state electrolyte LAGP synthesized in Example 1, indicating that the LAGP electrolyte was successfully prepared; Figure 3 Scanning electron microscope cross-section picture of the integrated positive electrode synthesized in Example 1, showing that the surface of the carbon nanotube loaded with copper metal was uniformly covered with a layer of succinonitrile-based solid-state electrolyte.

[0115] The battery performance was tested in a LAND CT2001A system using constant current charge-discharge technology, with a current density of 500 mA g -1 , a constant capacity of 1000 mAh g -1 , and a charge-discharge cut-off potential of 2.3-4.6 V. Figure 4 Charge-discharge curve of the solid-state lithium-carbon dioxide battery formed by Example 1, with charge-discharge potentials of 4.16 V and 3.05 V, respectively. Figure 5 Charge-discharge curve of the solid-state lithium-carbon dioxide battery formed by Example 1, showing that the battery loaded with copper catalyst can be reversibly cycled for 260 cycles.

[0116] Example 2

[0117] (1) After taking a slice of foamed nickel current collector with a size of 3*6 cm, wash it multiple times with acetone, ethanol, and water using ultrasonic cleaning for at least 10 min each time.

[0118] (2) Place 2.0 g of melamine on the bottom of a porcelain boat, put a layer of carbon paper in the middle, and then place the foamed nickel current collector on top. Heat it to 750°C at a heating rate of 5°C min -1 under N2 atmosphere, and keep it at this temperature for 2 h.

[0119] (3) Place the foamed nickel current collector with carbon material grown after annealing in anhydrous nickel chloride ethanol solution for rotary evaporation treatment at a rotation speed of 30 rpm min -1 .

[0120] (4) Dry the positive electrode slice and perform two high-temperature annealing treatments under N2 atmosphere. The first heat treatment parameters are a heating rate of 5°C min -1 to 350°C, keeping it at this temperature for 5 h, then take it out, wash it with ethanol, and dry it in a vacuum drying oven; the second heat treatment parameters are a heating rate of 2°C min -1 to 500°C, keeping it at this temperature for 5 h. The metal loading on the carbon nanotubes is 0.1%.

[0121] (5) Introduce the obtained electrode material into the succinonitrile-based solid-state electrolyte in situ under Ar atmosphere to form a continuous lithium ion transport layer.

[0122] First, 0.3 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is dissolved in 3 mL of anhydrous dimethyl sulfoxide (DMSO) and stirred at 60°C until the PVDF-HFP is completely dissolved; then, 0.16 g of lithium bis(trifluoromethanesulfonyl)imide and 0.2 g of stabilizer butylated hydroxytoluene (BHT) are added and continue to stir until dissolved; finally, 0.3 g of succinonitrile is added and continue to stir to obtain a uniform solution, then pour the uniform solution onto the electrode material prepared in step (4) and heat to 30°C in a glove box, dry for 50 h until the DMSO volatilizes, and finally, place it in a vacuum drying oven at 30°C for 50 h of drying treatment to obtain an integrated positive electrode.

[0123] (6) Battery assembly: Li 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO) as a solid-state electrolyte, an integrated positive electrode and metal Li as a negative electrode, respectively, and a layer of lithium bis(trifluoromethanesulfonyl)imide 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide protective film is coated between the positive electrode, negative electrode and solid-state electrolyte. Assemble the battery in a holey button cell.

[0124] Example 3

[0125] (1) Take a stainless steel mesh current collector slice with a size of 3*6 cm, and use acetone, ethanol, and water to ultrasonic clean multiple times, each time for at least 10 min.

[0126] (2) Place 3.0 g of melamine on the bottom of a porcelain boat, place a layer of carbon paper in the middle, and place the stainless steel mesh current collector on top. Heat to 800°C at a heating rate of 10°C / min -1 under N2 atmosphere, and keep the temperature for 3 h.

[0127] (3) Place the stainless steel mesh with carbon material grown after annealing in anhydrous copper chloride, anhydrous iron chloride, anhydrous nickel chloride, and anhydrous cobalt chloride ethanol solution for rotary evaporation treatment at a rotation speed of 60 rpm / min -1 .

[0128] (4) Dry the positive electrode sheet and perform two high-temperature annealing treatments under N2 atmosphere. The first heat treatment parameters are a heating rate of 10°C / min -1 to 350°C, keeping the temperature for 5 h, taking it out and washing with ethanol, and drying in a vacuum drying oven; the second heat treatment parameters are a heating rate of 5°C / min -1 to 550°C, keeping the temperature for 5 h. The metal loading on the carbon nanotubes is 20%, and the ratio of Cu:Fe:Ni:Co is 1:1:1:1.

[0129] (5) The obtained electrode material is introduced into the malononitrile-based solid-state electrolyte in situ under Ar atmosphere to form a continuous lithium ion transmission layer.

[0130] First, 0.6 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is dissolved in 5 mL of anhydrous dimethyl sulfoxide (DMSO) and stirred at 80°C until the PVDF-HFP is completely dissolved; then, 0.28 g of lithium bis(trifluoromethanesulfonyl)imide and 0.4 g of stabilizer butylated hydroxytoluene (BHT) are added and continue to stir until dissolved; finally, 0.7 g of malononitrile is added and continue to stir to obtain a uniform solution, then pour the uniform solution onto the electrode material prepared in step (4), heat in the glove box at a temperature of 60°C, dry for 60 h until the DMSO volatilizes, and finally, place it in a vacuum drying oven at 60°C for 60 h of drying treatment to obtain an integrated positive electrode.

[0131] (6) Battery assembly: Li 1.3 Al 0.3 Ti 1.7 P3O 12 (LATP) as a solid-state electrolyte, an integrated positive electrode and metal Li as a negative electrode, respectively, and a layer of 1-ethyl-3-methylimidazolium tetrafluoroborate protective film containing lithium tetrafluoroborate is coated between the positive electrode, negative electrode and solid-state electrolyte, and the battery is assembled in a holey button cell.

[0132] Example 4

[0133] (1) Take a stainless steel mesh current collector slice with a size of 3*6 cm, and clean it with acetone, ethanol and water for multiple times, each time for at least 10 min.

[0134] (2) Spread 3.0 g of melamine on the bottom of a porcelain boat, put a layer of carbon paper in the middle, and place the stainless steel mesh current collector on top, heat it to 800°C at a heating rate of 10°C / min under Ar atmosphere, and keep it at this temperature for 3 h. -1

[0135] (3) The obtained electrode material is introduced into the malononitrile-based solid-state electrolyte in situ under Ar atmosphere to form a continuous lithium ion transmission layer.

[0136] ​First, 0.4 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) was dissolved in 3 mL of anhydrous dimethyl sulfoxide (DMSO) and stirred at 60°C until the PVDF-HFP was completely dissolved; then, 0.15 g of lithium bis-trifluoromethanesulfonimide and 0.2 g of stabilizer butylated hydroxytoluene (BHT) were added and stirring was continued until dissolution; finally, 0.3 g of succinonitrile was added and stirring was continued to obtain a uniform solution, and then the uniform solution was poured onto the electrode material prepared in step (4) and dried at a temperature of 60°C in a glove box for 48 h until the DMSO evaporated, and finally, it was placed in a vacuum drying oven at 50°C for 48 h to obtain an integrated positive electrode.

[0137] (4) Battery assembly: LAGP as a solid-state electrolyte, integrated positive electrode and metal Li as positive and negative electrodes, respectively, and a layer of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl) imide protective film containing lithium bis-trifluoromethanesulfonimide was coated between the positive and negative electrodes. At this time, the metal loading on the positive electrode carbon nanotubes was 0. The battery was assembled in a button cell with a hole.

[0138] Figure 6 is a scanning electron microscope image of the integrated positive electrode synthesized in Example 4, and it can be seen that the carbon nanotube surface is uniformly covered with a layer of succinonitrile-based solid-state electrolyte.

[0139] The above is only a few embodiments of the present application, and does not limit the present application in any form. Although the present application is disclosed with the preferred embodiments as above, it is not intended to limit the present application. Any skilled person in the art can make some changes or modifications to the above disclosed technical content without departing from the scope of the technical solution of the present application, and such changes or modifications are equivalent to equivalent embodiments, and all belong to the scope of the technical solution.

Claims

1. An integrated positive electrode material, characterized by comprising: The integrated cathode material includes a current collector and a lithium-ion transport medium loaded on the current collector; Highly conductive carbon material is grown in situ on the surface of the current collector; The lithium-ion transport medium includes lithium.

2. The integrated positive electrode material of claim 1, wherein, The current collector also includes an active component, which includes active elements; Preferably, the active element is selected from at least one of copper, nickel, cobalt, and iron; Preferably, the current collector is selected from at least one of stainless steel mesh and nickel foam; Preferably, the carbon material grown in situ in the highly conductive carbon material is a carbon nanotube.

3. The method of producing an integrated positive electrode material according to any one of claims 1 to 2, characterized by, The preparation method includes the following steps: (1) Under an inactive atmosphere, nitrogen-containing compounds and current collectors are heat-treated and grown in situ to obtain current collectors containing highly conductive carbon materials. (2) A mixture of lithium salt, polymer matrix, stabilizer, solvent, additive, and current collector containing highly conductive carbon material is heated and dried to obtain the integrated cathode material.

4. The production method according to claim 3, characterized by, The preparation method includes the following steps: S1: Under an inactive atmosphere, nitrogen-containing compounds and current collectors are heat-treated and grown in situ to obtain current collectors containing highly conductive carbon materials. S2: Immerse the current collector containing highly conductive carbon material in a metal salt solution, rotary evaporate and dry it, and anneal it under an inactive atmosphere to obtain a current collector containing metal. S3: A mixture of lithium salt, polymer matrix, stabilizer, solvent, additive, and metal current collector is heated, dried (II), and further vacuum dried (III) to obtain the integrated cathode material.

5. The production method according to claim 4, characterized by, In step S1, the nitrogen-containing compound is selected from at least one of melamine, urea, and dicyandiamide; Preferably, the mass ratio of the nitrogen-containing compound to the current collector is (1.0–2.0 g): (0.3–0.5 g); Preferably, the in-situ growth heating rate is 2-10°C min -1 , the in-situ growth temperature is 600-800°C, and the in-situ growth time is 1-3h; Preferably, in step S2, the metal salt in the metal salt solution is selected from at least one of copper chloride, cobalt chloride, nickel chloride, and ferrous chloride; Preferably, the solvent in the metal salt solution is ethanol; Preferably, the metal loading on the metal current collector is 0.1% to 20%, and the metal loading is calculated based on the amount of metal salt in the metal salt solution; Preferably, the temperature of drying I is 50-80°C, and the drying time is 6-12 hours; Preferably, the annealing includes annealing I and annealing II; Preferably, the heating rate of said anneal I is comprised between 2 and 10°C / min -1 , the temperature of anneal I is comprised between 250 and 350°C, the time of anneal I is comprised between 2 and 5h; Preferably, the heating rate of the annealing II is 1-5°C / min -1 the temperature of the annealing II is 350-550°C, and the time of the annealing II is 2-5h; Preferably, in steps S1 and S2, the inactive atmosphere is independently selected from at least one of nitrogen and argon.

6. The preparation method according to claim 4, characterized in that, In step S3, the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate. Preferably, the polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene; Preferably, the stabilizer is butylated hydroxytoluene; Preferably, the solvent is dimethyl sulfoxide; Preferably, the additive is succinic anionyl nitrile; Preferably, the ratio of the polymer matrix, solvent, lithium salt, stabilizer, and additive is: (0.2–0.6 g): (2–5 mL): (0.1–0.28 g): (0.1–0.4 g): (0.2–0.7 g); Preferably, the temperature of drying II is 20–60°C, and the drying time is 36–60 h; Preferably, the temperature of the vacuum drying III is 20-60℃, and the time of the drying III is 36-60h.

7. An oxide-based solid-state lithium-carbon dioxide battery, characterized by, The oxide-based solid-state lithium-carbon dioxide battery comprises a positive electrode, a negative electrode, a solid-state electrolyte, an interface protection film and a battery shell; The interface protection film is arranged between the positive electrode and the solid-state electrolyte and between the negative electrode and the solid-state electrolyte, respectively; The positive electrode is selected from the integrated positive electrode material according to any one of claims 1-2; The negative electrode is metal lithium; The solid-state electrolyte is an oxide-type solid-state electrolyte; The battery shell is a positive electrode with a hole in a button cell.

8. The oxide-based solid-state lithium-carbon dioxide battery of claim 7, wherein, The oxide-type solid-state electrolyte is selected from Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.3 Al 0.3 Ti 1.7 P3O 12 , Li 6.4 La3Zr 1.4 Ta 0.6 O 12 at least one of.

9. The oxide-based solid-state lithium-carbon dioxide battery of claim 7, wherein, The interface protection film comprises lithium salt I and ionic liquid; Preferably, the lithium salt I is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate; Preferably, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate.

10. A method of producing an oxide-based solid-state lithium-carbon dioxide battery according to any one of claims 7 to 9, characterized in that, The preparation method comprises the following steps: (1) preparing an integrated positive electrode material; (2) assembling a battery in a positive electrode with a hole in a button cell to obtain the oxide-based solid-state lithium-carbon dioxide battery.